PENGARUH KOMPONEN INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERBANKAN (Studi pada Bank yang Terdaftar di Bursa Efek Indonesia pada Tahun 2019-2021) - Theofilus Kristian Besir; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2023)
The purpose of this study is to examine intellectual capital specifically about each component of the company’s intellectual capital can affect the company’s financial performance.Component of intellectual capital consist of four components are measured using MVAIC model, while financial performance is measured by return on assets (ROA), return on equity (ROE), and net interest margin (NIM). This study used company size and leverage as control variables. The population in this study are banking companies listed on the Indonesia Stock Exchange in the periode 2019-2021. Sampling was carried out using purposive sampling method which is sampling based on certain predetermined criteria. The total number of companies that are used as samples are 114 companies. The method of analysis in this study is the method of multiple linear analysis.The main results of this study indicate that the human capital efficiency (HCE) has a positive effect on company’s financial performance. Capital employed efficiency (CEE) has a positive effect on company’s financial performance. Relational capital efficiency (RCE) has a positive effect on company’s financial performance.